Accessibility and the ‘everyday mobility–work–household’ triad: an exploration during the COVID-19 crisis in low-income peripheries of Lima and Bogotá - (:unkn) unknown (Taylor & Francis, 2024)
How do people make decisions on where, when, and how to commute? And how did the pandemic crisis affect their commuting patterns? Based on exploratory interviews in Lima and family chronicles collected in Bogotá during 2020; and a second round of interv...
Keywords: Movilidad urbana; COVID-19